2019
DOI: 10.1128/aem.02091-18
|View full text |Cite
|
Sign up to set email alerts
|

TetR-Type Regulator SLCG_2919 Is a Negative Regulator of Lincomycin Biosynthesis in Streptomyces lincolnensis

Abstract: Lincomycin A (Lin-A) is a widely used antibacterial antibiotic fermented by Streptomyces lincolnensis. However, the transcriptional regulatory mechanisms underlying lincomycin biosynthesis have seldom been investigated. Here, we first identified a TetR family transcriptional regulator (TFR), SLCG_2919, which negatively modulates lincomycin biosynthesis in S. lincolnensis LCGL. SLCG_2919 was found to specifically bind to promoter regions of the lincomycin biosynthetic gene cluster (lin cluster), including 25 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
(48 reference statements)
2
39
0
Order By: Relevance
“…Meng et al (2017) revealed the regulatory network between nitrate metabolism and lincomycin biosynthesis where GlnR activates the transcription of lmrA , the lincomycin exporter gene. Lately, a TetR-type regulator SLCG_2919 has been identified as a repressor of lincomycin biosynthesis that controls the transcription of lmbA , lmbC , lmbE , lmbG , lmbK , lmbR , lmbV , and lmbW (Xu et al, 2019). However, to complete the regulatory network of lincomycin biosynthesis, there are lots of gaps remained.…”
Section: Introductionmentioning
confidence: 99%
“…Meng et al (2017) revealed the regulatory network between nitrate metabolism and lincomycin biosynthesis where GlnR activates the transcription of lmrA , the lincomycin exporter gene. Lately, a TetR-type regulator SLCG_2919 has been identified as a repressor of lincomycin biosynthesis that controls the transcription of lmbA , lmbC , lmbE , lmbG , lmbK , lmbR , lmbV , and lmbW (Xu et al, 2019). However, to complete the regulatory network of lincomycin biosynthesis, there are lots of gaps remained.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we have demonstrated that a global regulator BldA (Hou et al, 2018) and a CSR LmbU (Hou et al, 2017) are involved in lincomycin biosynthesis. Recently, a TetR-type regulator SLCG_2919 has been proved to negatively regulate lincomycin biosynthesis (Xu et al, 2018). However, the regulatory mechanism of lincomycin biosynthesis is still unclear at present.…”
Section: Discussionmentioning
confidence: 99%
“…The DNase I footprinting assay was performed as previously described (Xu et al, 2019a). To precisely determine the DNA binding site of SACE_0303, 100 ng FAM/HEX-labeled P 0303−0304 was successively incubated with 0, 70, and 490 nM His6-SACE_0303 in a total 50 µL of binding buffer at 20 • C for 20 min, and then 2 µL DNase I (1 U/µg; Promega) was performed at 20 • C for 30 s, 10 µL DNase I stop solution was added to the mixture and reacted at 65 • C for 10 min.…”
Section: Dnase I Footprinting Assaymentioning
confidence: 99%